Gene flow in the green mirid, Creontiades dilutus (Hemiptera: Miridae), across arid and agricultural environments with different host plant species. Issue 4 (25th February 2013) - Hereward, J. P.; Walter, G. H.; DeBarro, P. J.; Lowe, A. J.; Riginos, C.
Abstract: Creontiades dilutus (Stål), the green mirid, is a polyphagous herbivorous insect endemic to Australia. Although common in the arid interior of Australia and found on several native host plants that are spatially and temporally ephemeral, green mirids also reach pest levels on several crops in eastern Australia. These host‐associated dynamics, distributed across a large geographic area, raise questions as to whether (1) seasonal fluctuations in population size result in genetic bottlenecks and drift, (2) arid and agricultural populations are genetically isolated, and (3) the use of different host plants results in genetic differentiation. We sequenced a mitochondrial COI fragment from individuals collected over 24 years and screened microsatellite variation from 32 populations across two seasons. The predominance of a single COI haplotype and negative Tajima D in samples from 2006/2007 fit with a population expansion model. In the older collections (1983 and 1993), a different haplotype is most prevalent, consistent with successive population contractions and expansions. Microsatellite data indicates recent migration between inland sites and coastal crops and admixture in several populations. Altogether, the data suggest that long‐distance dispersal occurs between arid and agricultural regions, and this, together with fluctuations in population size, leads to temporally dynamic patterns of genetic differentiation. Host‐associated differentiation is evident between mirids sampled from plants in the genus Cullen (Fabaceae), the primary host, and alternative host plant species growing nearby in arid regions. Our results highlight the importance of jointly assessing natural and agricultural environments in understanding the ecology of pest insects. Abstract : The green mirid is endemic to arid parts of Australia, but has invaded agricultural resources within the last 200 years. We investigate gene flow across these two environments and conclude that the adaptations that allowed this insect to survive ephemeral conditions continue to determine patterns of genetic differentiation.